The neotropical genus Glyptoma Erichson, 1839 with description of new species and a key to the species (Coleoptera: Staphylinidae: Osorinae). - Irmler, Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 2015)
The Neotropical genus Glyptoma was revised with 18 species currently known from Central and South America. The following new species are described: G. rossii, G. simile, G. lescheni, G. guinanense, G. amazonense, G. schuhi. The following new synonyms are established: G. cicatricosa Motschulsky, 1857 = G. longipes Sharp, 1887; G. opacum (Sharp, 1876) = G. zischkai (Scheerpeltz, 1970); G. crassicorne Erichson, 1840 = G. cribellum Sharp, 1887; G. denieri (Bernhauer, 1939) = G. sanctaecatharinae (Scheerpeltz, 1970); G. nitens (Bernhauer, 1908) = G. reichenspergi (Scheerpeltz, 1970); G. nitidum (Bernhauer, 1908) = G. bolivianus (Scheerpeltz, 1970) and G. trinidadense Blackwelder, 1943. Glyptoma simplex (Wendeler, 1955) is transferred to the genus Espeson with the following new synonym established: Espeson simplex (Wendeler, 1955) = Espeson simplex Irmler, 2012. Keywords Neotropics, new species, key to species, Coleoptera: Staphylinidae: Osoriinae. Nomenclatural Acts bolivianus Scheerpeltz, 1970 (Calocerus), syn. n. of Glyptoma nitidum (Bernhauer, 1908) reichenspergi Scheerpeltz, 1970 (Calocerus), syn. n. of Glyptoma nitens (Bernhauer, 1908) sanctaecatharinae Scheerpeltz, 1970 (Calocerus), syn. n. of Glyptoma denieri (Bernhauer, 1939) zischkai Scheerpeltz, 1970 (Calocerus), syn. n. of Glyptoma opacum Sharp, 1876 simplex Irmler, 2012 (Espeson), syn. n. of Espeson simplex (Wendeler, 1955) simplex (Wendeler, 1955) (Espeson), comb. n. hitherto Calocerus simplex Wendeler, 1955 amazonense Irmler, 2015 (Glyptoma), spec. n. cicatricosa Motschulsky, 1857 (Glyptoma), LT cribellum Sharp, 1887 (Glyptoma), syn. n. of Glyptoma crassicorne Erichson, 1840 guianense Irmler, 2015 (Glyptoma), spec. n. laeviceps Sharp, 1887 (Glyptoma), LT lescheni Irmler, 2015 (Glyptoma), spec. n. longipes Sharp, 1887 (Glyptoma), syn. n. of Glyptoma cicatricosa Motschulsky, 1857 rossii Irmler, 2015 (Glyptoma), spec. n. schuhi Irmler, 2015 (Glyptoma), spec. n. simile Irmler, 2015 (Glyptoma), spec. n. trinidadense Blackwelder, 1943 (Glyptoma), syn. n. of Glyptoma nitidum (Bernhauer, 1908)